2022
DOI: 10.48550/arxiv.2206.10323
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What Makes Forest-Based Heterogeneous Treatment Effect Estimators Work?

Abstract: Estimation of heterogeneous treatment effects (HTE) is of prime importance in many disciplines, ranging from personalized medicine to economics among many others. Random forests have been shown to be a flexible and powerful approach to HTE estimation in both randomized trials and observational studies. In particular "causal forests", introduced by Athey, Tibshirani, and Wager (2019), along with the R implementation in package grf were rapidly adopted. A related approach, called "model-based forests", that is g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Dandl and colleagues compared honesty vs adaptive (not honest) forests in their simulations including causal forests and found that in their setting that was meant to represent an RCT, the adaptive forests performed better. 9 Additionally, honesty requires large sample sizes. Thus, we do not include honesty in the causal forests in the primary simulations but do investigate it in a second round of method comparisons.…”
Section: Causal Forestmentioning
confidence: 99%
“…Dandl and colleagues compared honesty vs adaptive (not honest) forests in their simulations including causal forests and found that in their setting that was meant to represent an RCT, the adaptive forests performed better. 9 Additionally, honesty requires large sample sizes. Thus, we do not include honesty in the causal forests in the primary simulations but do investigate it in a second round of method comparisons.…”
Section: Causal Forestmentioning
confidence: 99%
“…These advancements have expanded the potential applications of Causal Trees and their variants in academia and fields like healthcare, marketing and public policy, where personalising interventions can lead to better outcomes. In summary, Causal Trees provide a promising method for identifying and understanding heterogeneous causal effects (Dandl et al, 2022). This works particularly well for experiments and unconfoundedness because, in these cases, the effect estimates are based on treated and controls with similar values of the covariates.…”
Section: Causal Machine Learningmentioning
confidence: 99%